CRM Method in Improving Clothing Marketing at Irma Collection with Bootstrap 3 - Rahmawati, Rizki; Handayani, Masitah; Nofitri, Rika (Sistemasi: Jurnal Sistem Informasi, 2024)
The purpose of this research is to improve clothing marketing at Irma Collection with Bootstrap 3 because Irma Collection does not have a means or system to spread its products. Customers must come directly to the store, this causes customers to ask first about detailed information about the product so that it is less effective because there is no facility that helps customers to find out information about the product. Irma Collection really needs improvement, namely the construction of a system in order to provide good service and satisfy customer interest and make it easier for owners to recap reports on goods sold. With the Customer Relationship Management (CRM) system, it is expected that Irma Collection will be easier to attract many customers and maintain customer interest to become regular customers at Irma Collection.